COM programming with Microsoft .NET - Templeman, Julian (Microsoft Press, 2003)
Providing both theoretical and practical approaches, this in-depth programming guide explains how to interoperate between COM/COM+ and Microsoft® .NET. Coverage includes writing COM and COM+ code, disconnected applications, and new technologies in .NET.